Network Topological Analysis for the Identification of Novel Hubs in Plant Nutrition - Di Silvestre, Dario; Vigani, Gianpiero; Mauri, Pierluigi; Hammadi, Sereen; Morandini, Piero; Murgia, Irene (Frontiers in Plant Science, 2021)
Network analysis is a systems biology-oriented approach based on graph theory and recently adopted in various fields of life sciences. Starting from mitochondrial proteomes purified from roots of Cucumis sativus plants grown under single or combined iron (Fe) and molybdenum (Mo) starvation, we reconstructed and analysed at the topological level the Protein-Protein Interaction (PPI) and co-expression networks. Besides formate dehydrogenase (FDH), already known to be involved in Fe and Mo nutrition, other potential mitochondrial hubs of Fe and Mo homeostasis could be identified, such as the voltage-dependent anion channel VDAC4, the beta-cyanoalanine synthase/cysteine synthase CYSC1, the aldehyde dehydrogenase ALDH2B7 and the fumaryl acetoacetate hydrolase. Network topological analysis, applied to plant proteomes profiled in different single or combined nutritional conditions, can therefore assist in identifying novel players involved in multiple homeostatic interactions.